Exterior Door Design of Residental Buildings in Kurzeme and Zemagale in Classicism Era - Ozola, Silvija (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
Residential buildings from different eras constitute a large part of the urban architectural heritagein Kurzeme and Zemgale. The architecture of residential buildings at the end of 18th century and the beginning of 19th century was in fluenced by the classicism style. Buildings with a relatively simple structural design had a clear spatial structure. Special attention was paid to the overall image and the design of the central part of the facade and the main entrance. Entrance doors made by local craftsmen were a special accent of the facade of residential buildings. They characterized its residents and in dicated that the house belongs to a particular era. The goal of this work is to collect and systematize materials related to exterior doors of residential buildings, analyze the structure and proportions of door hinges and, as well as determine regional differences in their decorations. The basic methods to reach the goals are: inspection of exterior doors of residential buildings and their comparative analysis.